MENCIPTAKAN PEMBELAJARAN UNGGUL MELALUI MANAJEMEN BERBASIS SEKOLAH DI SMP ISLAM AL AZHAR 29 SEMARANG - Muhammad Alif Nuril 'Ibad; Fatkuroji Fatkuroji (Jurusan Manajemen Pendidikan Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2024)
This study aims to gather insights on implementing school-based management (SBM) in Islamic middle schools and analyze its impact on fostering superior learning environments. Data was collected from necessary parties using a qualitative research design, such as the school treasurer, deputy principal, and three instructors in charge of student affairs, curriculum, and public relations. The research was conducted at Al Azhar 29 Islamic Middle School in Semarang. Data collection methods included observations during learning activities, interviews with research subjects based on their roles and responsibilities concerning the management and implementation of the learning system, and document reviews related to the research topic. The collected data was analyzed using qualitative data analysis techniques, which involved identifying, organizing, describing, rearranging, and interpreting the data to derive meaningful insights. The findings reveal that SBM plays a crucial role in effectively, productively, and efficiently empowering resources within the school. Optimal management through the school management system is essential for effectively utilizing school resources. Critical components of creating quality and superior learning include financial management, curriculum development, educator and staff proficiency, infrastructure, community relations, pupil management, and school resilience. These findings suggest optimizing SBM can significantly create a superior learning environment. Therefore, further research is recommended to develop and refine effective and efficient SBM models.